PENERAPAN COMBINED COMPROMISE SOLUTION (COCOSO) METHOD DALAM SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MODEM - Daffa Arya; Yuyun Dwi Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Modem devices play a crucial role as the main infrastructure in ensuring the stability of computer network connectivity. The complexity of technical specifications and price variations in the commercial market often create decision bias for consumers. This study implements a decision support system using the Combined Compromise Solution (CoCoSo) method to objectively determine the priority of internet modem selection. The evaluation was conducted by involving seven multi-dimensional criteria, namely internet speed, network compatibility, modem type, number of users, battery capacity, security, and price and warranty components. Testing on seven popular modem alternatives was carried out through the integration of Weighted Sum Measure (WSM) and Weighted Product Measure (WPM) functions. The computational results show that alternative M4 (MQ531) obtained the highest preference value of 6.3689, making it the most optimal compromise solution. The implementation of this model is proven to minimize subjectivity and provide valid hardware investment recommendations for users.